Changes in bone marrow at upon dietary-induced weight loss - Spurny, Manuela; Jiang, Yixin; Sowah, Solomon A.; Schübel, Ruth; Nonnenmacher, Tobias; Bertheau, Robert; Kirsten, Romy; Johnson, Theron S.; Hillengaß, Jens; Schlett, Christopher L.; Stackelberg, Oyunbileg von; Ulrich, Cornelia; et al. (Nutrients, 2020)
BACKGROUND: Bone marrow fat is implicated in metabolism, bone health and haematological diseases. Thus, this study aims to analyse the impact of moderate weight loss on bone marrow fat content (BMFC) in obese, healthy individuals. - METHODS: Data of the HELENA-Trial (Healthy nutrition and energy restriction as cancer prevention strategies: a randomized controlled intervention trial), a randomized controlled trial (RCT) among 137 non-smoking, overweight or obese participants, were analysed to quantify the Magnetic Resonance Imaging (MRI)-derived BMFC at baseline, after a 12-week dietary intervention phase, and after a 50-week follow-up. The study cohort was classified into quartiles based on changes in body weight between baseline and week 12. Changes in BMFC in respect of weight loss were analysed by linear mixed models. Spearman's coefficients were used to assess correlations between anthropometric parameters, blood biochemical markers, blood cells and BMFC. - RESULTS: Relative changes in BMFC from baseline to week 12 were 0.0 ± 0.2%, -3.2 ± 0.1%, -6.1 ± 0.2% and -11.5 ± 0.6% for Q1 to Q4. Across all four quartiles and for the two-group comparison, Q1 versus Q4, there was a significant difference (p < 0.05) for changes in BMFC. BMFC was not associated with blood cell counts and showed only weaker correlations (<0.3) with metabolic biomarkers. - CONCLUSION: Weight loss is associated with a decrease of BMFC. However, BMFC showed no stronger associations with inflammatory and metabolic biomarkers.